Non-indigenous linguistic and cultural elements in the poetry of B. Kanapyanov (Eurasian Journal of Philology Science and Education, 2016)
This article is about the features of the establishment and functioning of the non-indigenous linguistic and cultural elements in the works B. Kanapyanov. It is noted that the system of individual artistic works of B. Kanapyanov was developed in a distinctive contextual environment. In paticular, it is language environment of Russian-speaking Kazakh poetry with the active collaboration of the two linguistic systems and two national and linguistic pictures of the world. One of the consequences of such interaction is the introduction of foreign linguistic and cultural elements into Russian artistic text that belongs to native and ethnically primary language of the bilingual poet. These elements are introduced at different levels of the works of the poet and perform various stylistic functions and have different characteristics that depend on its linguistic status and form of the appearance within the text. Cooperation Russian and Kazakh branches of our literature is recognized as beneficial.
Keywords: national; non-indigenous; Russian-speaking Kazakh poets; linguistic and cultural elements; bilingual poet; Kazakh lexeme.